Factors affecting compliance of intraoperative frozen and final histopathology in borderline ovarian tumors: Retrospective cohort study - Baykuş, Yakup; Deniz, Rulin; Çelik Kavak, Ebru (Journal of Surgery and Medicine, 2019)
Aim: Frozen sections (FS) are commonly used in the course of adnexal masses operations, and it assist to select the most appropriate surgical treatment modalities in addition to intraoperative management. In this study, we aimed to investigate the effect of the demographic and obstetric characteristics as well as biochemical findings with the consistency of intraoperative FS findings with the final histopathological diagnosis in patients with borderline ovarian tumors (BOT). Methods: This retrospective study included a total of 31 BOT patients who underwent intraoperative frozen histopathological study. The study population was divided into two groups; group 1 consisted of patients who had a positive concordance between the findings of intraoperative FS and the final histopathology, while the patients included in the group 2 had a negative concordance between the results of two examinations. We compared two groups in terms of baseline characteristics, tumor markers, tumor size, bilaterality, menopausal status and presence of ascites. Results: There were no statistically significant differences between the two groups in terms of age, body-mass index, tumor markers (CA125, CA19-9, CEA, AFP, CA15-3, β-HCG) and tumor size (P=0.74, P=0.55, P=0.87, P=0.55, P=0.24, P=0.33, P=0.70, P=0.32 and P=0.98, respectively). Also, the presence of bilateral BOT and ascites as well as menopausal status were not different between both groups (P=0.12, P=0.60, P=0.70, respectively). Conclusion: Based on the study findings, we noted that patients whether had concordance or discordance with the findings of intraoperative frozen sections and the final histopathology did not differ in terms of baseline characteristics and tumor markers.